Implementasi Electronic Government pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Boyolali - Fachmika Pradita Putri; Is Hadri Utomo (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
Public services utilizing advances in Information and Communication Technology (ICT) are crucial in this current era. This study aims to determine the implementation of Electronic Government at the Office of Investment and One Stop Service (DPMPTSP) Boyolali Regency. The main problem at this time is that the telecommunication network is not evenly distributed in Boyolali Regency and the regulations from the center that often change make the implementation of e-government in the form of online licensing services to be hampered. The method used in this research is descriptive qualitative. This study uses Edward III's Implementation Theory for data analysis consisting of communication, resources, disposition, and bureaucratic structure. This research is an implementation study that has never been done before in DPMPTSP Boyolali Regency. The results of the study show that DPMPTSP Boyolali Regency in implementing E-government in the form of online licensing services using SIPP and OSS has been implemented quite well, which can be seen from the fulfillment of the four Edward III Implementation Theories. However, there are still some things that need to be improved, including the provision of supporting regulations, adding human resources, improving facilities and stabilizing the budget.